Literasi Keuangan Sebagai Strategi untuk Memperkuat Pemahaman dan Kesadaran Keuangan di Kalangan Siswa SMA Generasi Z (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing variety of digital financial products has contributed to greater access to financial services. However, there is growing need to enhance financial literacy, particularly among Generation Z, which dominates the use of technology compared to other generations. This generation is highly proficient in utilizing technology, including financial technology, which facilitates economic transactions through digital transfers and payments. On the other hand, this convenience also creates financial vulnerabilities for Generation Z, as reflected in poor personal fianncial management that leads to consumptive behavior and engagenment in online lending. Moreover, Generation Z tends to have lower levels of financial literacy compared to other generations. This community service program was conducted for Generation Z, specifically senior high school students at SMA Averos in Sorong City. The activity aimed to improve students’ understanding of financial literacy and provide practical tips for effective financial management. The program was implemented in the form of a financial literacy socialization activity, with the expectation of fostering financial awareness among young people regarding the importance of managing their finances and developing positive financial attitudes. The results of this activity indicate that students were able to understand financial literacy concepts effectively, leading to increased awareness and the ability to manage their finances in a prudent and responsible manner.